PEMODELAN STRATEGIS GREEN-DIGITAL BANKING DALAM IMPLEMENTASI ESG UNTUK KINERJA KEBERLANJUTAN BANK PEMBANGUNAN DAERAH INDONESIA: STUDI EMPIRIS BERBASIS PLS-SEM - Muhammad Alfarizi (Jurnal Ilmu Administrasi Bisnis, 2026)
Abstract: Environmental protection has become a major focus due to degradation leading to increased occurrences of extreme natural events. The UN Agenda 2030 emphasizes sustainability goals with the principle of "leaving no one behind," encouraging countries, including Indonesia, to adopt sustainable practices. Regional Development Banks (BPD) play a crucial role in sustainability through green banking and support for environmentally-friendly projects. This study explores the impact of green banking practices and fiscal decentralization on the implementation of Environmental, Social, and Governance (ESG) principles and the sustainable performance of BPD in Indonesia. The study uses a quantitative approach through survey questionnaires targeting Low-Middle Management at ten productive BPDs in Indonesia. The research focuses on green finance, fiscal decentralization, green banking practices, ESG initiatives, and sustainable performance. Data is analyzed using PLS-SEM to test validity, reliability, and hypothesis path estimates. The results indicate that Green Finance has a significant positive impact on ESG initiatives by reinforcing commitment to sustainable development through environmentally-friendly investments. Fiscal decentralization enhances local government autonomy, local financial governance, and the partnership between BPD and local governments for sustainability. Meanwhile, green banking practices strengthen the integration of sustainability principles into bank operations. ESG initiatives have proven effective in improving sustainable performance and serve as a mediating variable. BPD is advised to expand ESG initiatives by increasing investment in environmentally-friendly projects, developing sustainable financial products, and issuing green bonds. Implementing green banking practices, employee training, and transparency in ESG reporting are also crucial. The government and LPS should strengthen regulations and oversight to support sustainability.Abstraksi: Perlindungan lingkungan kini menjadi fokus utama karena degradasi yang menyebabkan peningkatan kejadian alam ekstrem. Agenda PBB 2030 menggarisbawahi tujuan keberlanjutan dengan prinsip "tidak meninggalkan siapa pun," mendorong negara-negara termasuk Indonesia untuk menerapkan praktik berkelanjutan. Bank Pembangunan Daerah (BPD) memainkan peran krusial dalam keberlanjutan melalui green banking dan dukungan terhadap proyek ramah lingkungan. Penelitian ini mengeksplorasi pengaruh praktik green banking dan desentralisasi fiskal terhadap implementasi prinsip Environmental, Social, and Governance (ESG) serta kinerja berkelanjutan BPD di Indonesia. Studi ini menggunakan pendekatan kuantitatif melalui survei kuesioner pada Low-Middle Management sepuluh Bank BPD Produktif di Indonesia. Fokus penelitian meliputi green finance, desentralisasi fiskal, praktik green banking, inisiatif ESG dan kinerja berkelanjutan. Data dianalisis menggunakan PLS-SEM untuk menguji validitas, reliabilitas, dan estimasi jalur hipotesis. Hasil penelitian menunjukkan Green Finance berpengaruh positif signifikan terhadap inisiatif ESG dengan memperkuat komitmen terhadap pembangunan berkelanjutan melalui investasi ramah lingkungan. Desentralisasi fiskal meningkatkan otonomi pemerintah daerah, tata kelola keuangan lokal dan kemitraan BPD-Pemerintah Daerah untuk kepentingan keberlanjutan. sementara Praktik green banking memperkuat integrasi prinsip keberlanjutan dalam operasional bank. Inisiatif ESG terbukti efektif dalam meningkatkan kinerja berkelanjutan dan berperan sebagai variabel mediasi. Bank BPD disarankan untuk memperluas inisiatif ESG dengan meningkatkan investasi dalam proyek ramah lingkungan, mengembangkan produk keuangan berkelanjutan, dan menerbitkan obligasi hijau. Penerapan praktik Green Banking, pelatihan karyawan, serta transparansi pelaporan ESG juga penting. Pemerintah dan LPS harus memperkuat regulasi dan pengawasan untuk mendukung keberlanjutan.